Urban Test (TCT-DP) as an Instrument that Identifies Specifics of Creativity of Young Adolescents with Different Types of Giftedness - Donii E.I (Moscow State University of Psychology and Education, 2022)
This article presents the results of the study of the Urban test as an instrument for identifying the specifics of the manifestation of creativity in younger adolescents with artistic and intellectual giftedness. The literature notes the specificity of the manifestation of creativity in younger adolescents with these types of giftedness. The author notes that the analysis of indicators of the Urban test categories, regardless of its general indicator, suggests that they can reveal the specifics of the manifestation of creativity in younger adolescents with artistic and intellectual giftedness. The study involved 196 younger adolescents, of whom 63 intellectually gifted (M = 11.6 years old, 30 boys and 33 girls), 34 artistically gifted (M = 12.1 years old, 5 boys and 29 girls) and 99 from the control group (M = 11.6 years, 46 boys and 53 girls). Analysis of the average values of the Urban test indicators revealed statistically significant intergroup differences in categories such as humor, non-traditional use - any manipulation of the form; any surreal, fictional and/or abstract use of elements or patterns; any use of symbols and signs, and speed. For the first time, an attempt was made to analyze the values of the Urban test categories, regardless of its overall value in the context of identifying the specifics of the manifestation of creativity in young adolescents with artistic and intellectual giftedness. The results expand the toolbox for specialists, clarifying the capabilities of an already familiar test, and allowing to optimize the diagnostic process.